1345 Asbestos-related diseases in curitiba: the brazil-italy project. (24th April 2018) - Consonni, D; Puchalski Kalinke, LP; Kalinke, MA; D'Almeida Miranda, FMoura; Marcondes, L; Hallfeld, T; Brey, C; Boller, S; Pesatori, AC; Mensi, C; Sarquis, LMMansano
Abstract : Introduction: Brazil is one of the major producers of chrysotile, a well-known carcinogen, but few studies evaluated its impact locally. For these reasons, a joint project, supported by CAPES, Brasilia, was started between the Federal University of Paranà (UFPR), Curitiba, Brazil, and the Fondazione IRCCS Ca' Granda, Milan, Italy. Methods: The objects of the joint project include: a cohort mortality study among asbestos–cement workers in the Curitiba Metropolitan Region; the implementation of a registry of malignant mesothelioma (MM) in Curitiba based on the Italian model. MM cases are already collected (1998–2012) in the Curitiba Population-Based Cancer Registry (RCBP); but information on asbestos exposure is unavailable and diagnostic accuracy of MM has never been evaluated. For this reason, we translated the Italian standardised questionnaire on asbestos exposure and are implementing the database for MM cases in Portuguese. Clinical documentation of adult subjects with ICD-10 codes C45 (mesothelioma), C38 (mediastinal and pleural cancers), and C48 (peritoneal cancers) in the RCBP will be examined to evaluate diagnostic accuracy. Results: The questionnaire has been preliminarily tested on 40 workers in Curitiba. The software has been translated and adapted. Review of clinical records of 269 subjects is in progress; we identified about 20% of death certificate only cases. For the cohort study, we obtained lists of workers employed since the beginning of production in three asbestos-cement factories. We identified about 4000 workers, 2300 with valid date of birth. Conclusion: For the cohort study, we are exploring the existence of additional sources to complete missing information and contacting relevant institutions to perform the mortality follow-up. Within 2018 we foresee to have the questionnaire ready for use, the software implemented, and the clinical documentation review completed. This international collaboration is an important step towards a better assessment of the impact of chrysotile use in Brazil.